Structural and functional analysis of the human POT1-TPP1 telomeric complex - Cory Rice (Nature Portfolio, 2017)
POT1 and TTP1 are part of the shelterin complex that caps and stabilizes the ends of telomeres. Here the authors present a structural analysis of the human POT1-TTP1 complex, shedding light on how it assembles and how cancer-associated mutations impact its assembly and function.